Strategy for Strengthening Organizational Culture Based on Islamic Values and the Role of Students in Pesantren - Rohmaniyah, Naila; Munir, Munir; Syawaludin, Mohammad; Hamidah, Hamidah; Torik, Muhammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study explores strategies to strengthen organizational culture based on Islamic values and the role of students at Pondok Pesantren Aulia Cendikia Talang Jambe Palembang. Using a qualitative approach with a case study method, primary data was collected through interviews with kiai, ustadz, administrators, santri, alumni, and the local community. Secondary data was gathered from books, journals, research reports, articles, and related documents. Data was analyzed using thematic analysis and the interactive model of Miles and Huberman. The results show that organizational culture is formed through externalization, objectification, and internalization in pesantren life. Externalization is seen in religious, academic, and social activities; objectification is found in rules, traditions, and organizational structures; and internalization is reflected in students' behavior, making them more disciplined, responsible, and morally aware. The leadership of the kiai, role modeling, and consistent habituation are key factors in strengthening the organizational culture. Additionally, integrating traditional and modern curricula shows the pesantren's ability to preserve core values while adapting to modern changes. These findings highlight the importance of organizational culture in shaping student character and provide a reference for managing adaptive and sustainable Islamic education.